1997
DOI: 10.1103/physreve.55.7565
|View full text |Cite
|
Sign up to set email alerts
|

Envelope analysis of intense relativistic quasilaminar beams in rf photoinjectors:mA theory of emittance compensation

Abstract: In this paper we provide an analytical description for the transverse dynamics of relativistic, space-chargedominated beams undergoing strong acceleration, such as those typically produced by rf photoinjectors. These beams are chiefly characterized by a fast transition, due to strong acceleration, from the nonrelativistic to the relativistic regime in which the initially strong collective plasma effects are greatly diminished. However, plasma oscillations in the transverse plane are still effective in signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
233
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(238 citation statements)
references
References 12 publications
2
233
1
2
Order By: Relevance
“…Figure 5 shows the qualitative consistency between the analytic contour from (14) and data points obtained through GENESIS simulations for the specific case of ¼ 0. Figure 6 shows the relative difference between the analytic and simulated fits, given by F ¼ 1 À k i F = k i .…”
Section: Simulation and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 shows the qualitative consistency between the analytic contour from (14) and data points obtained through GENESIS simulations for the specific case of ¼ 0. Figure 6 shows the relative difference between the analytic and simulated fits, given by F ¼ 1 À k i F = k i .…”
Section: Simulation and Resultsmentioning
confidence: 99%
“…The FEL simulation code GENESIS 1.3 [18] was used to evaluate the accuracy of the fitting formula in (14). Nearly 14 000 time-independent simulations were performed using a large range of rms transverse electron beam sizes order to sample a significant portion of the scaled parameter space where the analytical model is applicable (see Table I).…”
Section: Simulation and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the semi-analytic code HOMDYN [9], a wide range of injector parameters was investigated earlier under the constraints imposed by the invariant-envelope [10] matching condition: injection into the matched accelerating gradient of the booster at a laminar waist. As a result, it was found that by adjusting the gun solenoid strength so that the waist also occurs when the emittance has its relative maximum, the second emittance maximum can be shifted to higher energy with a lower final emittance value than previously achieved [2,11].…”
Section: Simulationsmentioning
confidence: 99%
“…This critical process is governed by the nonlinear envelope equation addressed shortly. The first beam-envelope theory of emittance compensation is based on perturbative treatment of space-charge-dominated beam evolution in constant focusing channels nearby a special quasiequilibrium solution, known as the invariant envelope [3,4]. For spacecharge-dominated beams, the invariant envelope is analogous to Brillouin flow for nonaccelerating beams, where focusing and defocusing forces are balanced to produce a stable beam.…”
Section: Introductionmentioning
confidence: 99%